Teacher’s Perception toward the Teaching and Learning Science and Mathematics in English at Secondary School - Yahya, Hairi (2006)
The era of globalization has great influence on education in Malaysia. As such the teaching of Mathematics and Science in English was implemented to face new challenges in education. This study is an attempt to explore teacher’s perception towards the implementation of English in Teaching Mathematic and Science (ETeMS). Data was collected from 110 Mathematics and Science teachers from 18 secondary schools in Temerloh, Pahang. Descriptive statistic analysis (frequency, percentage, min) and inferential statistic ( correlation) were used to analyses data by using the Statistic Package for Social Science (SPSS) version 11.5. The finding show that teachers gave a positive agreement toward the implementation of ETeMS. Similar results were obtained regarding teachers agreement toward the teaching and learning , in service training, the level of support from principals and the teaching aids. ETeMS teacher’s perceive their English Language proficiency as being at a moderate level. There is a poor significant correlation between teachers background and the teachers perception towards the implementation of ETeMS. Several suggestions are raised such as schools should provide in house training at school level to upgrade teachers proficiency in English. The quality of teaching courseware also need to be upgraded.